Paolo Nori, Bassotuba non c’è: caratteristiche stilistiche, formali, grammaticali e retoriche del romanzo a confronto con il Salto mortale di Luigi Malerba, precursore delle opere della letteratura emiliana - Ludmann, Ágnes (Verbum – Analecta Neolatina, 2012)
In the current study, I would like to present and examine the novel Bassotuba non c’è, which made Paolo Nori, the Emilian writer successful. The novel was written in 1999 and isread and loved for its language, structure and theme. Nori is one of the so-called Emilian writers (members of this unorganized and spontaneous literary group are Gianni Celati, Daniele Benati, Ugo Cornia, Ermanno Cavazzoni, and Luigi Malerba), whose purpose is to modernize novels and make them more accessible for readers by using an almost spoken-style language, abandoning classical, decorated and rigid language, and also reconstructing and breaking the classical narrative structure.